2015
DOI: 10.1007/s10899-015-9565-7
|View full text |Cite
|
Sign up to set email alerts
|

Breaks in Play: Do They Achieve Intended Aims?

Abstract: Breaks in play represent a responsible gambling strategy designed to disrupt states of dissociation and enhance the likelihood of drawing attention to a player's session behaviour and expenditure with respect to time and money. The aim of the break in play is to motivate the player to modify or cease gambling so the activity remains within affordable levels. The aim of this study was to investigate whether imposed breaks in play in the absence of accompanying warning messages were effective in reducing craving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 35 publications
1
43
2
1
Order By: Relevance
“…Cooling-off periods have been claimed to be a useful responsible gambling tool to facilitate a period of time where the player can reflect on their gambling behaviour, with the aim of reducing compulsive gambling and chasing financial losses (Williams et al 2012). However, there is a lack of consensus about the frequency and duration in breaks of play, which would provide most robust protection to the gambling population (Blaszczynski et al, 2016). Cooling-off periods were defined as a period of less than six months of duration by Bonello and Griffiths (2017).…”
Section: Responsible Gambling Toolsmentioning
confidence: 99%
“…Cooling-off periods have been claimed to be a useful responsible gambling tool to facilitate a period of time where the player can reflect on their gambling behaviour, with the aim of reducing compulsive gambling and chasing financial losses (Williams et al 2012). However, there is a lack of consensus about the frequency and duration in breaks of play, which would provide most robust protection to the gambling population (Blaszczynski et al, 2016). Cooling-off periods were defined as a period of less than six months of duration by Bonello and Griffiths (2017).…”
Section: Responsible Gambling Toolsmentioning
confidence: 99%
“…It is important to note that these breaks in gambling practice must be sufficiently long in order to have an the level of cognitive distortions. Indeed, Blaszczynski, Cowley, Anthony, and Hinsley (2015) have previously demonstrated that short breaks, of a few minutes, during gambling activities could have a counterproductive effect by increasing craving. The ability to implement a gambling-free period of at least a month could encourage gamblers to put things into perspective and to exit the vicious circle of cognitive distortions, especially by getting out of a loss cycle (which one could correlate to the chasing item).…”
Section: Discussionmentioning
confidence: 99%
“…This stands in contrast with a wider literature on breaks in play, although Blaszczynski et al . () note these include additional interventions that require gamblers to think about their play and it may be the content of these messages that drive reappraisal of gambling behaviour. Similarly, James, O'Malley, and Tunney (), in studying the role of inter trial intervals in gambling behaviour, found that perseverative gambling during extinction in a simulated slot machine game was affected by the amount of inter trial interval participants were exposed to; longer intertrial intervals were associated with gambling in the face of continued losses, particularly at lower rates of reinforcement.…”
Section: Behavioural Mechanismsmentioning
confidence: 99%
“…It is presently disputed whether this also affects the suppression or extinction of learned behaviours (Bouton et al, 2014;Gallistel & Gibbon, 2000) in the same manner, although there is increasing evidence to support this (Bouton et al, 2014;Moody et al, 2006). There is already evidence within the gambling literature to suggest that this prediction is already partially realized; Blaszczynski, Cowley, Anthony, and Hinsley (2015) found that craving to gamble increased in line with intersession interval on a simulated slot machine game. While they provided an explanation based on theories of behavioural completion, this finding can be adequately described with an associative learning-based account.…”
Section: Behavioural Mechanismsmentioning
confidence: 99%